Case report: A gain-of-function of hamartin may lead to a distinct “inverse TSC1-hamartin” phenotype characterized by reduced cell growth - Praticò, Andrea D.; Falsaperla, Raffaele; Comella, Mattia; Belfiore, Giuseppe; Polizzi, Agata; Ruggieri, Martino (Frontiers in Pediatrics, 2023)
Mutations of TSC1 and TSC2 genes cause classical Tuberous Sclerosis Complex (TSC), a neurocutaneous disorder characterized by a tendency to develop hamartias, hamartomas and other tumours. We herein report on a girl, now aged 5 years, who presented a previously unreported, distinct clinical phenotype consisting in primary microcephaly (head circumference = 40 cm, -5.6 standard deviations), brain anomalies including hypoplasia of the corpus callosum (with a residual draft of the genu), simplified parieto-temporal gyral pattern, colpocephaly with ectasia of the temporal ventricular horns, intellectual disability and a general pattern of reduced growth (with weight and height < 3rd centiles). No classical features of TSC were recorded; the girl harbored a novel missense variant in TSC1 (c.611G>A). We hypothesize that her clinical phenotype could be related to a “gain-of-function” of the TSC1 protein product hamartin, causing an increase of function of the protein effects on inhibition of its intracellular targets (i.e., mTORC or RAC1 pathways), causing a distinct “inverse TSC1-hamartin” phenotype characterized by reduced growth of cells instead of the more classical predisposition to increased cell growth.